α-Synuclein Radiotracer Development and In Vivo Imaging: Recent Advancements and New Perspectives - Obada M. Alzghool; van Dongen Goos; van de Giessen Elsemarike; Schoonmade Linda; Beaino Wissam (WILEY, 2022)
α-Synucleinopathies including idiopathic Parkinson's disease, dementia with Lewy bodies and multiple systems atrophy share overlapping symptoms and pathological hallmarks. Selective neurodegeneration and Lewy pathology are the main hallmarks of α-synucleinopathies. Currently, there is no imaging biomarker suitable for a definitive early diagnosis of α-synucleinopathies. Although dopaminergic deficits detected with single-photon emission computed tomography (SPECT) and positron emission tomography (PET) radiotracers can support clinical diagnosis by confirming the presence of dopaminergic neurodegeneration, dopaminergic imaging cannot visualize the preceding disease process, nor distinguish α-synucleinopathies from tauopathies with dopaminergic neurodegeneration, especially at early symptomatic disease stage when clinical presentation is often overlapping. Aggregated α-synuclein (αSyn) could be a suitable imaging biomarker in α-synucleinopathies, because αSyn aggregation and therefore, Lewy pathology is evidently an early driver of α-synucleinopathies pathogenesis. Additionally, several antibodies and small molecule compounds targeting aggregated αSyn are in development for therapy. However, there is no way to directly measure if or how much they lower the levels of aggregated αSyn in the brain. There is clearly a paramount diagnostic and therapeutic unmet medical need. To date, aggregated αSyn and Lewy pathology inclusion bodies cannot be assessed ante-mortem with SPECT or PET imaging because of the suboptimal binding characteristics and/or physicochemical properties of current radiotracers. The aim of this narrative review is to highlight the suitability of aggregated αSyn as an imaging biomarker in α-synucleinopathies, the current limitations with and lessons learned from αSyn radiotracer development, and finally to propose antibody-based ligands for imaging αSyn aggregates as a complementary tool rather than an alternative to small molecule ligands. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.